Thermostable ZIF-8 nanocrystal and one-pot synthesis method thereof
By optimizing the raw material ratio of ZIF-8 nanocrystals and adopting a one-pot synthesis method, thermally stable ZIF-8 nanocrystals were prepared, which solved the problem of structural degradation at high temperatures and achieved structural integrity under high temperature conditions. and suitability for industrial applications.
Patent Information
- Application Number
- CN202411536878.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-21
AI Technical Summary
The existing ZIF-8 nanocrystals have structural degradation, surface area loss and reduced active sites at high temperatures, limiting their applicability in industrial processes.
By optimizing the ratio of 2-methylimidazole and zinc nitrate hexahydrate and selecting an appropriate organic co-solvent, a one-pot synthesis method was used to prepare thermally stable ZIF-8 nanocrystals. The method includes dissolving 2-methylimidazole and zinc nitrate hexahydrate in deionized water respectively, mixing and ultrasonic dispersing with an organic co-solvent, then dropping a metal solution, stirring to synthesize, and obtaining nanocrystals through centrifugal separation and drying.
The thermal stability and structural stability of ZIF-8 nanocrystals are improved, enabling them to maintain structural integrity under high temperatures and harsh conditions, and are suitable for use in gas separation, catalysis, storage and other fields.
Smart Images

Figure CN119331263A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of ZIF-8 nanocrystals, and in particular to a thermally stable ZIF-8 nanocrystal and a one-pot synthesis method thereof. Background Art
[0002] Metal-organic framework (MOF) is a new type of energy-saving organic / inorganic hybrid porous material with large internal surface area, framework uniformity, permanent porosity, structural stability and excellent tunability. Therefore, as a cutting-edge material, MOF successfully overcomes the structural defects encountered by traditional porous materials (such as activated carbon, zeolite and silica) due to insufficient structural tunability.
[0003] Zeolitic imidazolate frameworks (ZIFs) are a subclass of MOFs that have attracted extensive attention worldwide due to their large surface area, ultrahigh porosity, excellent crystallinity, and structural stability. Among ZIFs, ZIF-8 is the most recognized and widely used member of the ZIF family. ZIF-8 is generated by the self-assembly behavior of metal ions (zinc; M) and imidazolate linkers (2-methylimidazole; 2-mim), following the formation of M-2-mim-M with a ratio of M:2-mim of 1:70. The strong interaction between the tetrahedrally linked zinc metal ions (Zn2+) and the nitrogen (N) on the aromatic rings of the organic linkers gives rise to a sodalite topology similar to zeolites.
[0004] In view of the above prior art, the inventors found that the existing synthesized ZIF-8 nanocrystals will rapidly undergo structural degradation, surface area loss and a reduction in the number of available active sites at high temperatures, which greatly limits their applicability in some important industrial processes. Since gas separation, catalytic reactions, especially some membrane-assisted reactors and challenging separations, which usually require ≥180°C, are not suitable for use in the above environments. Summary of the invention
[0005] Based on the technical problems existing in the above-mentioned prior art, the present invention provides a thermally stable ZIF-8 nanocrystal and a one-pot synthesis method thereof.
[0006] In the first aspect, the present application provides a thermally stable ZIF-8 nanocrystal, using the following technical solution: A thermally stable ZIF-8 nanocrystal is prepared by including the following materials in parts by weight: 2-methylimidazole 10-15 parts; 4-8 parts of zinc nitrate hexahydrate; 75-80 parts of organic co-solvent.
[0007] Through the above technical scheme, the present application optimizes the ratio of raw materials, especially the ratio of 2-methylimidazole and zinc nitrate hexahydrate, which helps to optimize the formation conditions of ZIF-8, thereby improving its thermal stability. This material can maintain its structural integrity under high temperature and harsh conditions, and is suitable for applications requiring high temperature treatment. In addition, the selection of organic co-solvents can effectively improve the polarity and solubility of the solvent, promote the crystal growth of ZIF-8, and then affect its crystal morphology and performance, so that the final product has better physical and chemical properties.
[0008] Furthermore, the organic co-solvent includes any one of methanol, ethanol, n-hexane, cyclohexane, n-heptane and / or n-dodecane.
[0009] Through the technique scheme, the application specifically specifies the composition of the organic co-solvent, and the key to the selection of these solvents is its solubility and compatibility to the part and metal ion in the reaction process. Alcoholic solvents have good polarity and solubility, can effectively form stable coordination complexes with 2-methylimidazole, and promote the dissolving of zinc source simultaneously. And alkane solvents have lower polarity, help to improve the form and the crystallinity of nanocrystals. In addition, the mixed use of different solvents can regulate the polarity of reaction medium, makes the synthesis of ZIF-8 more efficient, and the nanocrystals finally obtained have more superior thermal stability and structural stability.
[0010] In a second aspect, the present application provides a one-pot synthesis method of thermally stable ZIF-8 nanocrystals, using the following technical scheme: A one-pot synthesis method of thermally stable ZIF-8 nanocrystals comprises the following synthesis steps: 2-Methylimidazole and zinc nitrate hexahydrate are placed in deionized water respectively, stirred and mixed, and a ligand solution and a metal solution are collected; After mixing the organic co-solvent and the ligand solution, ultrasonically disperse and collect the dispersed emulsion; The metal solution is added dropwise to the dispersed emulsion, and after the addition is completed, the co-solvent-ligand-water emulsion is collected; The co-solvent-ligand-water emulsion is placed at room temperature, stirred for synthesis, and the lower layer of precipitate is separated by centrifugation, washed, and dried to prepare the thermally stable ZIF-8 nanocrystal.
[0011] Through the above technical scheme, the present application dissolves 2-methylimidazole and zinc nitrate hexahydrate in deionized water respectively, and the obtained ligand solution and metal solution can ensure the uniformity of the reactants. The viscosity of methanol and ethanol as co-solvents is relatively high, which prevents the easy diffusion of reagent molecules in the synthetic mixture, and can well solve the problem of incomplete phase development of ZIF-8. Ultrasonic dispersion effectively reduces the aggregation degree of particles in the solution, enhances the contact between reactants, and thus promotes the formation of ZIF-8. At the same time, organic solvents with smaller chain lengths show better solvent-water hydrogen bond formation ability, thereby improving the interaction between water-miscible straight-chain co-solvents and reagent molecules.
[0012] The advantage of this one-pot method is that it simplifies the synthesis process, reduces the intermediate steps, and improves the synthesis efficiency. Finally, through centrifugal separation and drying, high-purity ZIF-8 nanocrystals can be obtained, which meet the requirements of thermal stability and structural integrity and are suitable for applications in gas separation, catalysis and storage.
[0013] Furthermore, the particle size of the ZIF-8 nanocrystals is (0.30±0.03) μm-(0.50±0.03) μm.
[0014] Through the above technical scheme, the ZIF-8 nanocrystals prepared in this application have a uniform and moderate particle size. By controlling the synthesis conditions, such as reaction time, temperature and stirring speed, it is possible to achieve accurate regulation of the particle size, thereby improving its reactivity and adsorption performance. In the gas separation and catalytic process, the size of the particles determines its contact efficiency and diffusion rate with the reactants, ensuring that the final product has excellent performance in the application. In addition, the precise control of the particle size also helps to improve the thermal stability of ZIF-8 under different environments, ensure its structural stability under high temperature and high pressure conditions, and adapt to diverse industrial needs.
[0015] Furthermore, the ultrasonic dispersion is carried out at 80-120W for 100-150min.
[0016] Through the above technical scheme, the application optimizes the specific parameters of ultrasonic dispersion, and by performing ultrasonic dispersion at a specific power and time, the uniformity and dispersibility of the reactants can be significantly improved, thereby promoting the crystallization process of ZIF-8. Appropriate ultrasonic power and time can avoid excessive particle fragmentation caused by excessive energy introduction, thereby ensuring the integrity and stability of the final crystal structure of ZIF-8. This process not only improves the synthesis efficiency, but also can regulate the morphology and size distribution of nanocrystals to a certain extent, further optimizing its performance.
[0017] Furthermore, the mass fraction of the ligand solution is 25-37.5%.
[0018] Furthermore, the mass fraction of the metal solution is 10-20%.
[0019] Furthermore, in the stirring synthesis, the stirring speed is 450-550 rpm and the stirring time is 0-24 h.
[0020] Furthermore, the drying treatment temperature is 55-65°C.
[0021] Through the above technical scheme, the present application optimizes the preparation process parameters, and the appropriate concentration can balance the reaction rate and the crystallization process to avoid the aggregation or unevenness of particles caused by too fast crystallization. At the same time, the concentration of the ligand will also affect the coordination environment of the metal ion, and then affect the final structure and performance of ZIF-8. Therefore, by adjusting the mass fraction of the ligand solution, accurate control of the performance of ZIF-8 nanocrystals can be achieved to meet different application requirements.
[0022] In summary, this application has the following beneficial effects: First, the present application optimizes the ratio of raw materials, especially the ratio of 2-methylimidazole and zinc nitrate hexahydrate, which helps to optimize the formation conditions of ZIF-8, thereby improving its thermal stability. This material can maintain its structural integrity under high temperature and harsh conditions, and is suitable for applications requiring high temperature treatment. In addition, the selection of organic co-solvents can effectively improve the polarity and solubility of the solvent, promote the crystal growth of ZIF-8, and then affect its crystal morphology and performance, so that the final product has better physical and chemical properties.
[0023] Second, the application specifically specifies the composition of the organic co-solvent, and the key to the selection of these solvents is its solubility and compatibility to the part and metal ion in the reaction process. Alcoholic solvents have good polarity and solubility, can effectively form stable coordination complexes with 2-methylimidazole, and promote the dissolving of zinc source simultaneously. And alkane solvents have lower polarity, help to improve the form and crystallinity of nanocrystals. In addition, the mixed use of different solvents can regulate the polarity of reaction medium, makes the synthesis of ZIF-8 more efficient, and the nanocrystals finally obtained have more superior thermal stability and structural stability.
[0024] Third, the present application is by dissolving 2-methylimidazole and zinc nitrate hexahydrate in deionized water respectively, and the obtained ligand solution and metal solution can ensure the uniformity of the reactants. For methanol and ethanol, the viscosity as co-solvents is relatively high, which prevents the easy diffusion of reagent molecules in the synthetic mixture, and can well solve the incomplete stability of ZIF-8 phase development. Ultrasonic dispersion effectively reduces the aggregation degree of particles in the solution, enhances the contact between reactants, thereby promoting the formation of ZIF-8. At the same time, organic solvents with smaller chain lengths show better solvent-water hydrogen bond formation ability, thereby improving the interaction between water-miscible straight-chain co-solvents and reagent molecules. The advantage of this one-pot method is that it simplifies the synthesis process, reduces intermediate steps, and improves synthesis efficiency. Finally, by centrifugation and drying, high-purity ZIF-8 nanocrystals can be obtained, which meet the requirements of thermal stability and structural integrity, and are suitable for application in the fields of gas separation, catalysis and storage. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a SEM image of ZIF prepared using methanol in Example 1 of the present application; Figure 2 This is a SEM image of ZIF prepared using ethanol in Example 4 of the present application; Figure 3 This is a SEM image of ZIF prepared using n-hexane in Example 5 of the present application; Figure 4 This is a SEM image of ZIF prepared using cyclohexane in Example 6 of the present application; Figure 5 This is a SEM image of ZIF prepared using n-heptane in Example 7 of the present application; Figure 6 This is a SEM image of ZIF prepared using n-dodecane in Example 8 of the present application. DETAILED DESCRIPTION
[0026] The present application is further described in detail below with reference to the embodiments.
[0027] In the examples of the present application, the raw materials and instruments used are as follows, but not limited thereto. Raw materials not otherwise specified are of analytical grade.
[0028] Example 1 A thermally stable ZIF-8 nanocrystal comprises the following raw materials: 10 kg 2-methylimidazole, 4 kg zinc nitrate hexahydrate and 75 kg organic co-solvent methanol.
[0029] A one-pot synthesis method for thermally stable ZIF-8 nanocrystals comprises the following preparation steps: 2-Methylimidazole and zinc nitrate hexahydrate were placed in 400 kg of deionized water, stirred and mixed, and a ligand solution and a metal solution were collected; After mixing the organic co-solvent methanol with the ligand solution, the mixture was subjected to ultrasonic dispersion treatment at 80W for 100min and the dispersed emulsion was collected; The metal solution is added dropwise to the dispersed emulsion, and after the addition is completed, the co-solvent-ligand-water emulsion is collected; The co-solvent-ligand-water emulsion was placed at room temperature, stirred at 450 rpm for 8 hours, centrifuged at 6500 rpm to separate the lower precipitate, washed with methanol, and dried at 60° C. for 12 hours to prepare the thermally stable ZIF-8 nanocrystals.
[0030] Example 2 A thermally stable ZIF-8 nanocrystal comprises the following raw materials: 13 kg 2-methylimidazole, 6 kg zinc nitrate hexahydrate and 77 kg organic co-solvent methanol.
[0031] A one-pot synthesis method for thermally stable ZIF-8 nanocrystals comprises the following preparation steps: 2-Methylimidazole and zinc nitrate hexahydrate are placed in 450 kg of deionized water respectively, stirred and mixed, and a ligand solution and a metal solution are collected; The organic co-solvent methanol was mixed with the ligand solution, and then subjected to ultrasonic dispersion treatment at 100 W for 120 min and the dispersed emulsion was collected; The metal solution is added dropwise to the dispersed emulsion, and after the addition is completed, the co-solvent-ligand-water emulsion is collected; The co-solvent-ligand-water emulsion was placed at room temperature, stirred at 500 rpm for 12 hours, centrifuged at 6500 rpm to separate the lower precipitate, washed with methanol, and dried at 60° C. for 12 hours to prepare the thermally stable ZIF-8 nanocrystals.
[0032] Example 3 A thermally stable ZIF-8 nanocrystal comprises the following raw materials: 15 kg 2-methylimidazole, 8 kg zinc nitrate hexahydrate and 80 kg organic co-solvent methanol.
[0033] A one-pot synthesis method for thermally stable ZIF-8 nanocrystals comprises the following preparation steps: 2-Methylimidazole and zinc nitrate hexahydrate were placed in 500 kg of deionized water respectively, stirred and mixed, and a ligand solution and a metal solution were collected; After mixing the organic co-solvent methanol with the ligand solution, the mixture was subjected to ultrasonic dispersion treatment at 120W for 150min and the dispersed emulsion was collected; The metal solution is added dropwise to the dispersed emulsion, and after the addition is completed, the co-solvent-ligand-water emulsion is collected; The co-solvent-ligand-water emulsion was placed at room temperature, stirred at 550 rpm for 24 hours, centrifuged at 6500 rpm to separate the lower precipitate, washed with methanol, and dried at 60° C. for 12 hours to prepare the thermally stable ZIF-8 nanocrystals.
[0034] Example 4 A thermally stable ZIF-8 nanocrystal comprises the following raw materials: 13 kg 2-methylimidazole, 6 kg zinc nitrate hexahydrate and 77 kg organic co-solvent ethanol.
[0035] A one-pot synthesis method for thermally stable ZIF-8 nanocrystals comprises the following preparation steps: 2-Methylimidazole and zinc nitrate hexahydrate are placed in 450 kg of deionized water respectively, stirred and mixed, and a ligand solution and a metal solution are collected; The organic co-solvent methanol was mixed with the ligand solution, and then subjected to ultrasonic dispersion treatment at 100 W for 120 min and the dispersed emulsion was collected; The metal solution is added dropwise to the dispersed emulsion, and after the addition is completed, the co-solvent-ligand-water emulsion is collected; The co-solvent-ligand-water emulsion was placed at room temperature, stirred at 500 rpm for 12 hours, centrifuged at 6500 rpm to separate the lower precipitate, washed with methanol, and dried at 60° C. for 12 hours to prepare the thermally stable ZIF-8 nanocrystals.
[0036] Example 5 A thermally stable ZIF-8 nanocrystal comprises the following raw materials: 13 kg 2-methylimidazole, 6 kg zinc nitrate hexahydrate and 77 kg organic co-solvent n-hexane.
[0037] A one-pot synthesis method for thermally stable ZIF-8 nanocrystals comprises the following preparation steps: 2-Methylimidazole and zinc nitrate hexahydrate are placed in 450 kg of deionized water respectively, stirred and mixed, and a ligand solution and a metal solution are collected; The organic co-solvent methanol was mixed with the ligand solution, and then subjected to ultrasonic dispersion treatment at 100 W for 120 min and the dispersed emulsion was collected; The metal solution is added dropwise to the dispersed emulsion, and after the addition is completed, the co-solvent-ligand-water emulsion is collected; The co-solvent-ligand-water emulsion was placed at room temperature, stirred at 500 rpm for 12 hours, centrifuged at 6500 rpm to separate the lower precipitate, washed with methanol, and dried at 60° C. for 12 hours to prepare the thermally stable ZIF-8 nanocrystals.
[0038] Example 6 A thermally stable ZIF-8 nanocrystal comprises the following raw materials: 13 kg 2-methylimidazole, 6 kg zinc nitrate hexahydrate and 77 kg organic co-solvent cyclohexane.
[0039] A one-pot synthesis method for thermally stable ZIF-8 nanocrystals comprises the following preparation steps: 2-Methylimidazole and zinc nitrate hexahydrate are placed in 450 kg of deionized water respectively, stirred and mixed, and a ligand solution and a metal solution are collected; The organic co-solvent methanol was mixed with the ligand solution, and then subjected to ultrasonic dispersion treatment at 100 W for 120 min and the dispersed emulsion was collected; The metal solution is added dropwise to the dispersed emulsion, and after the addition is completed, the co-solvent-ligand-water emulsion is collected; The co-solvent-ligand-water emulsion was placed at room temperature, stirred at 500 rpm for 12 hours, centrifuged at 6500 rpm to separate the lower precipitate, washed with methanol, and dried at 60° C. for 12 hours to prepare the thermally stable ZIF-8 nanocrystals.
[0040] Example 7 A thermally stable ZIF-8 nanocrystal comprises the following raw materials: 13 kg 2-methylimidazole, 6 kg zinc nitrate hexahydrate and 77 kg organic co-solvent n-heptane.
[0041] A one-pot synthesis method for thermally stable ZIF-8 nanocrystals comprises the following preparation steps: 2-Methylimidazole and zinc nitrate hexahydrate are placed in 450 kg of deionized water respectively, stirred and mixed, and a ligand solution and a metal solution are collected; The organic co-solvent methanol was mixed with the ligand solution, and then subjected to ultrasonic dispersion treatment at 100 W for 120 min and the dispersed emulsion was collected; The metal solution is added dropwise to the dispersed emulsion, and after the addition is completed, the co-solvent-ligand-water emulsion is collected; The co-solvent-ligand-water emulsion was placed at room temperature, stirred at 500 rpm for 12 hours, centrifuged at 6500 rpm to separate the lower precipitate, washed with methanol, and dried at 60° C. for 12 hours to prepare the thermally stable ZIF-8 nanocrystals.
[0042] Example 8 A thermally stable ZIF-8 nanocrystal comprises the following raw materials: 13 kg 2-methylimidazole, 6 kg zinc nitrate hexahydrate and 77 kg organic co-solvent n-dodecane.
[0043] A one-pot synthesis method for thermally stable ZIF-8 nanocrystals comprises the following preparation steps: 2-Methylimidazole and zinc nitrate hexahydrate are placed in 450 kg of deionized water respectively, stirred and mixed, and a ligand solution and a metal solution are collected; The organic co-solvent methanol was mixed with the ligand solution, and then subjected to ultrasonic dispersion treatment at 100 W for 120 min and the dispersed emulsion was collected; The metal solution is added dropwise to the dispersed emulsion, and after the addition is completed, the co-solvent-ligand-water emulsion is collected; The co-solvent-ligand-water emulsion was placed at room temperature, stirred at 500 rpm for 12 hours, centrifuged at 6500 rpm to separate the lower precipitate, washed with methanol, and dried at 60° C. for 12 hours to prepare the thermally stable ZIF-8 nanocrystals.
[0044] Performance Testing The ZIF-8 nanocrystals prepared in Examples 1-8 were subjected to differential scanning calorimetry to test their thermal stability, specifically to detect their surface defects: The results are shown in Table 1 below: Table 1 Performance test table
[0045] From the above examples 1-8, combined with Table 1 and Figure 1-6 By comparing the test results, we can find that: The present application optimizes the proportion of raw materials by the present application, particularly the ratio of 2-methylimidazole and zinc nitrate hexahydrate, which helps to optimize the formation conditions of ZIF-8, thereby improving its thermal stability. At the same time, the present application effectively reduces the aggregation degree of particles in the solution by ultrasonic dispersion, strengthens the contact between the reactants, thereby promoting the formation of ZIF-8. At the same time, the organic solvent with smaller chain length shows better solvent-water hydrogen bond formation ability, thereby improving the interaction between water-miscible straight-chain co-solvent and reagent molecules. The advantage of this one-pot method is that it simplifies the synthesis process, reduces intermediate steps, and improves synthesis efficiency. Finally, by centrifugation and drying, it is possible to obtain high-purity ZIF-8 nanocrystals, which meet the requirements of thermal stability and structural integrity.
[0046] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.
[0047] All publications, patent applications, patents and other references mentioned in this specification are incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings conventionally understood by those skilled in the art. In the event of a conflict, the definition in this specification shall prevail.
[0048] When this specification uses the prefix "well-known to those skilled in the art", "prior art" or similar terms to introduce materials, substances, methods, steps, devices or components, etc., the objects introduced by the prefix cover those commonly used in the art when this application is filed, but also include those that are not commonly used at present but will become recognized in the art as being suitable for similar purposes.
[0049] In the context of the present specification, any matters or items not mentioned are directly applicable to those known in the art without any changes except those explicitly stated.
Claims
1. A thermally stable ZIF-8 nanocrystal, characterized in that: The composition comprises the following materials in parts by weight: 2-methylimidazole 10-15 parts; 4-8 parts of zinc nitrate hexahydrate; 75-80 parts of organic co-solvent.
2. A thermally stable ZIF-8 nanocrystal according to claim 1, characterized in that, The organic co-solvent includes any one of methanol, ethanol, n-hexane, cyclohexane, n-heptane and / or n-dodecane.
3. A one-pot synthesis method of a thermally stable ZIF-8 nanocrystal according to claim 1 or 2, characterized in that, The synthesis steps include: 2-Methylimidazole and zinc nitrate hexahydrate are placed in deionized water respectively, stirred and mixed, and a ligand solution and a metal solution are collected; After mixing the organic co-solvent and the ligand solution, ultrasonically disperse and collect the dispersed emulsion; The metal solution is added dropwise to the dispersed emulsion, and after the addition is completed, the co-solvent-ligand-water emulsion is collected; The co-solvent-ligand-water emulsion is placed at room temperature, stirred for synthesis, and the lower layer of precipitate is separated by centrifugation, washed, and dried to prepare the thermally stable ZIF-8 nanocrystal.
4. A one-pot synthesis method of a thermally stable ZIF-8 nanocrystal according to claim 3, characterized in that, The particle size of the ZIF-8 nanocrystals is (0.30±0.03) μm-(0.50±0.03) μm.
5. The one-pot synthesis method of a thermally stable ZIF-8 nanocrystal according to claim 3, characterized in that: The ultrasonic dispersion is carried out at 80-120W for 100-150min.
6. The one-pot synthesis method of a thermally stable ZIF-8 nanocrystal according to claim 3, characterized in that: The mass fraction of the ligand solution is 25-37.5%.
7. The one-pot synthesis of thermally stable ZIF-8 nanocrystals according to claim 3, characterized in that: The mass fraction of the metal solution is 10-20%.
8. The one-pot synthesis of thermally stable ZIF-8 nanocrystals according to claim 3, characterized in that: The stirring speed in the stirring synthesis is 450-550 rpm, and the stirring time is 0-24 h.
9. The one-pot synthesis method of a thermally stable ZIF-8 nanocrystal according to claim 3, characterized in that: The drying treatment temperature is 55-65°C.
Citation Information
Cited By
Normal hexane modified ZIF-95 composite nanofiber membrane and preparation method thereof
CN120662133A
A n-hexane modified zif-95 composite nanofiber membrane and a preparation method thereof
CN120662133B